Manipulation of Edge‐Site Fe–N2 Moiety on Holey Fe, N Codoped Graphene to Promote the Cycle Stability and Rate Capacity of Li–S Batteries. (9th December 2018) - Wang, Yazhou; Adekoya, David; Sun, Jiqing; Tang, Tianyu; Qiu, Hailong; Xu, Li; Zhang, Shanqing; Hou, Yanglong
Abstract: Graphene‐based materials have been widely studied to overcome the hurdles of Li–S batteries, but suffer from low adsorptivity to polar polysulfide species, slow mass transport of Li + ions, and severe irreversible agglomeration. Herein, via a one‐step scalable calcination process, a holey Fe, N codoped graphene (HFeNG) is successfully synthesized to address these problems. Diverging by the holey structures, the Fe atoms are anchored by four N atoms (Fe–N4 moiety) or two N atoms (Fe–N2 moiety) localized on the graphene sheets and edge of holes, respectively, which is confirmed by X‐ray absorption spectroscopy and density functional theory calculations. The unique holey structures not only promote the mass transport of lithium ions, but also prohibit the transportation of polysulfides across these additional channels via strong adsorption forces of Fe–N2 moiety at the edges. The as‐obtained HFeNG delivers a high rate capacity of 810 mAh g −1 at 5 C and a stable cycling performance with the capacity decay of 0.083% per cycle at 0.5 C. The concept of holey structure and introduction of polar moieties could be extended to other carbon and 2D nanostructures for energy storage and conversion devices such as supercapacitors, alkali‐ion batteries, metal–air batteries, and metal–halogen batteries. Abstract : A holey Fe, N codoped graphene (HFeNG) is developed via a scalable fabrication process that can "dig" holes onto the graphene and "modify" the edge of the holes with the Fe–N 2 moiety. The HFeNG could not only accelerate Li + transportation but also prohibit the transportation of polysulfides and therefore deliver high rate capacities and a stable cycling performance.